Directly observed treatment short-course in management of peripheral tubercular lymphadenitis - Khuntdar, Bidyut Kumar; Roy, Arghya Kamal; Gayen, Biplab Kumar; Sau, Manabendra (Asian Journal of Medical Sciences, 2022)
Background: Tuberculosis (TB) is a major public health problem worldwide. It is one of the main causes of infectious disease and mortality, especially in the developing countries, and has been recognized as one of the top ten causes of death worldwide by the World Health Organization. Aims and Objectives: The aims of this study were to assess clinical pattern and efficacy of Directly Observed Treatment Short-Course (DOTS) in management of peripheral tubercular lymphadenitis. Materials and Methods: This was a prospective, observational study among pediatric peripheral tubercular lymphadenitis patients to assess the clinical pattern, investigations, and treatment outcome. Results: In this study, 72 patients having peripheral tubercular lymphadenitis were enrolled. Most cases had cervical node involvement (81%). Discharging sinus was found in 28.98% cases. Acid-fast bacillus (AFB) was detected by fine needle aspiration and cytology (FNAC) in 21 cases (30.43%). Among them, pulmonary TB was found in two cases (9.52%), one patient being sputum positive. After treatment completion, lymph node(s) enlargement persisted in 6 (8.69%) cases, of which two patients (2.89%) had persistent discharging sinus. On repeat FNAC, acid-fast bacilli were seen in two patients. Success rate was 91.3% confirming the efficacy of DOTS in the management of tubercular lymphadenitis. Conclusions: Cervical lymphadenitis was found to be most common type of peripheral lymphadenitis. Cytopathology from the suspected lymph nodes had better success rate than AFB detection or CBNAAT of FNAC samples for diagnosing tubercular etiology in the study. DOTS strategy was effective for peripheral tubercular lymphadenitis with high success rate in this study.